Pressure-sensitive adhesive, preparation method thereof and application of pressure-sensitive adhesive in high-temperature-resistant zero-climbing large-size polaroid protective film
By using cellulose derivative modified acrylate polymer, the problem of peeling force climbing of the protective film of large-sized polarizer is solved, and the stability of low-speed and high-speed peeling force and surface resistivity is improved, and it is suitable for protective film applications under high temperature resistance.
Patent Information
- Application Number
- CN202411741676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
During the production, transportation and assembly of large-sized polarizers, the peeling force of the protective film is easily climbed after a long period of bonding, resulting in a significant increase in the high-speed peeling force, which may lead to damage to the polarizer and display module.
Cellulose derivative modified acrylate polymer is used as the main component of the pressure-sensitive adhesive, and mixing it with antistatic agent, wetting agent and isocyanate-based curing agent to form a rubber layer with high crosslinking density, which improves the overall strength and modulus of the protective film and reduces the creep of the rubber layer.
The low-speed peeling force and high-speed peeling force of the protective film under high temperature conditions are achieved to climb less than 30%, and the surface resistivity and tear film voltage are stable, which are suitable for large-size polarizer protective films that are resistant to high temperature "0" climb.
Smart Images

Figure BDA0005162738880000071 
Figure BDA0005162738880000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optical protective films, and specifically relates to a pressure-sensitive adhesive and a preparation method thereof, and an application in a high-temperature resistant "0" climb large-size polarizer protective film. Background Art
[0002] Polarizer is one of the key materials for LCD screen display and plays a decisive role in the screen display quality. The LCD panel has two polarizers, one of which acts as a polarizer and the other as an analyzer. The two polarizers exist at the same time for the LCD to display images. Therefore, it can be said that the quality of the polarizer determines the image quality of the entire display screen. The transportation and processing of polarizers during the production process and screen assembly process will cause bumps, scratches, embossing, stains, etc. on its surface, which seriously reduces the quality of the polarizer.
[0003] In order to ensure the display quality of the screen, polarizer protective film came into being. The function of polarizer protective film is to protect the quality of the polarizer and reduce the influence of external force or other factors on the polarizer.
[0004] During the production, storage, transportation, screen assembly, circulation and processing of polarizers, a protective film is attached to the surface of the polarizer to prevent damage and contamination of the polarizer. The protective film is a part of the polarizer and is inspected as a whole. Therefore, the protective film attached to the surface is required to have good light transmittance and low haze. At the same time, the protective film is required to be firmly attached to the polarizer, free of bubbles, impurities, crystal points, etc.
[0005] After the assembly of the LCD display is completed, the protective film on the surface of the polarizer will be torn off. In order to improve production efficiency, the assembly plant can now tear off the protective film at a speed of up to 30m / min. At the same time, the screen size is relatively large, so a huge tearing force will be generated in the process of tearing off the protective film at high speed. This tearing force is called high-speed peeling force. Under normal circumstances, the speed of testing the peeling force of the protective film is 0.3m / min. In the case of high-speed peeling force requirements, the peeling force with a test speed of 0.3m / min is called low-speed peeling force. Taking ordinary protective film as an example, when the low-speed peeling force is 5gf / 25mm, the high-speed peeling force can reach 200gf / 25mm, which is more than 40 times the low-speed peeling force. According to the 60-inch screen size, the high-speed peeling force will exceed 6000gf. Under such a huge peeling force, a huge tearing voltage will be generated, causing the module insulation layer to be broken down. Excessive tearing force will cause the polarizer and even the display module to be torn and deformed. In addition, the possibility of the glue layer on the protective film falling off and transferring to the surface of the polarizer is greatly increased. In view of this situation, large-size display module assembly plants have strict requirements on the peeling force of polarizer protective films at low speeds (0.3m / min) and high speeds (30m / min), while also having low surface resistance and tearing voltage.
[0006] In addition, from the moment the protective film is attached to the surface of the polarizer, it goes through the processing, packaging, warehousing, and logistics transportation of the polarizer manufacturer, and then to the screen factory for assembly. By the time the protective film is finally torn off, the protective film has been attached to the surface of the polarizer for several months. During this period, the pressure-sensitive adhesive layer of the protective film will undergo various processing steps. At the same time, the adhesive layer will produce creep, which makes the final peeling force for tearing off the protective film much higher than the initial peeling force, and it may even be difficult to tear off, eventually resulting in the scrapping of the screen and causing huge economic losses.
[0007] In order to effectively solve the problem of increased peeling force of the protective film, patent CN115926694A proposes adding a certain proportion of cellulose ester to the commercially available acrylic pressure-sensitive adhesive. After being subjected to high temperature of 80°C*1h, the peeling force increases slightly, but the initial peeling force is lower than 3gf / 25mm and cannot be applied to large-size polarizers. At the same time, no high-speed peeling force data is given. The experimental results show that the compatibility of cellulose molecules and acrylic resin is limited, and the coated film will precipitate after long-term storage, resulting in a decrease in optical performance. Patent CN102746810A solves the balance between low-speed peel force and high-speed peel force by preparing an adhesive composition with C4-C10 (meth) acrylates, hydroxyl-containing copolymerizable monomers, carboxyl-containing copolymerizable monomers, trifunctional isocyanate compounds, crosslinking inhibitors, crosslinking catalysts, and polyether-modified siloxane compounds. The peel force rises by less than 1.5 times of the original peel force after aging. However, the protective film prepared by the patent does not mention whether it has antistatic function and the test conditions are 60℃*90%RH*250h, which can no longer meet the increasingly high requirements for polarizer protective films on the market. Summary of the invention
[0008] In view of this, the present application aims to overcome the deficiencies in the prior art and provide a pressure-sensitive adhesive and a preparation method thereof and an application in a high-temperature resistant "0" climb large-size polarizer protective film, so as to solve the problem of excessive climb of high-speed peeling force and low-speed peeling force when peeling off the protective film after long-term lamination of the current large-size polarizer protective film. While solving the peeling force climb, the surface resistivity and the film tearing voltage are not affected.
[0009] The present invention is achieved through the following technical solutions:
[0010] A pressure-sensitive adhesive comprising the following components in parts by weight:
[0011] 80-100 parts of cellulose derivative modified acrylate polymer, 1-3 parts of curing agent, 1-5 parts of antistatic agent, 0.5-3 parts of wetting agent and 30-50 parts of first solvent;
[0012] The cellulose derivative modified acrylate polymer is obtained by free radical polymerization of acrylate hard monomer, acrylate soft monomer, acrylate functional monomer, cellulose derivative containing double bonds, initiator and second solvent.
[0013] The present invention obtains cellulose derivative modified acrylate polymer by copolymerizing acrylate hard monomer, acrylate soft monomer, acrylate functional monomer and cellulose derivative containing double bonds, and forms a three-dimensional spatial network structure through the reaction of active hydroxyl groups provided on the polymer chain and isocyanate curing agent, thereby improving the overall cross-linking density of the adhesive layer; the introduction of cellulose molecules increases the structural stability of the acrylate polymer molecules, thereby improving the overall strength and modulus of the adhesive layer in the protective film, reducing the creep of the adhesive layer, and the peeling force climbs very little after cooling, and a low high-speed peeling force can still be obtained. The pressure-sensitive adhesive prepared by the cellulose derivative modified acrylate polymer is particularly suitable for preparing large-size polarizer protective films with high temperature resistance "0" climb requirements.
[0014] Preferably, the acrylic acid ester hard monomer is one or more of acrylic acid, methacrylic acid, methyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, vinyl acetate, styrene, and acrylonitrile.
[0015] Preferably, the acrylic ester soft monomer is one or more of 2-ethylhexyl acrylate, isooctyl acrylate, n-butyl acrylate, isobutyl acrylate, nonyl acrylate, dodecyl acrylate, octadecyl acrylate, and cyclohexyl methacrylate.
[0016] Preferably, the acrylate functional monomer is one of hydroxyethyl acrylate, hydroxypropyl acrylate, 1,6-hexanediol diacrylate, 2-methoxyethyl acrylate, polyethylene glycol diacrylate, 3-ethoxyethyl acrylate, and 2-phenoxyethyl acrylate.
[0017] Preferably, the cellulose derivative containing double bonds is obtained by reacting an acyl halide compound containing double bonds with a hydroxyl group in the cellulose derivative.
[0018] Preferably, the double-bonded acyl halide compound comprises any one or more of acryloyl chloride, crotonoyl chloride, methacryloyl chloride, 4-vinylbenzoyl chloride, acryloyl bromide, crotonoyl bromide, methacryloyl bromide, and 4-vinylbenzoyl bromide.
[0019] Preferably, the cellulose derivative comprises one or a mixture of two of cellulose acetate butyrate, cellulose acetate propionate, ethyl cellulose and methyl cellulose.
[0020] Preferably, the first solvent and the second solvent are any one or two of ethyl acetate, butanone, cyclohexanone, toluene, acetone, and methyl isobutyl ketone.
[0021] Preferably, the antistatic agent is an ionic liquid antistatic agent; more preferably, it is any one of FC4400 of 3M, AP-8 and IL-P14 of Japan KRONOI Chemical, and HZ02 of Hubei Shengsaino.
[0022] Preferably, the wetting agent is a polyether-modified organosiloxane, preferably any one of SY5066 and SY5084 produced by Yangzhou Weina New Materials Co., Ltd. and TSI 316 produced by Evonik Degussa.
[0023] Preferably, the curing agent is a trifunctional isocyanate curing agent; more preferably, it is any one or two of toluene diisocyanate (TDI) trimer, 4,4'-diphenylmethane diisocyanate (MDI) trimer, polyphenyl polymethylene polyisocyanate (PAPI) trimer, hexamethylene diisocyanate (HDI) trimer, and isophorone diisocyanate (IPDI) trimer.
[0024] Preferably, the initiator can make the above-mentioned acrylic ester hard monomer, soft monomer, functional monomer, and homemade cellulose derivative containing double bonds copolymerize. The present application does not limit the specific type of the initiator, and the initiator conventionally used in the industry can be selected.
[0025] In addition, to achieve the above object, the present invention also provides a method for preparing a pressure-sensitive adhesive, comprising the following steps:
[0026] S1 Preparation of cellulose derivative modified acrylate polymer:
[0027] (1) firstly, uniformly mix the acrylic acid ester hard monomer, the acrylic acid ester soft monomer, the acrylic acid ester functional monomer, and the cellulose derivative containing double bonds, and dissolve the initiator in the second solvent to prepare a 5% initiator solution for standby use;
[0028] (2) In a four-necked flask equipped with an electric stirrer, a condenser, a N2 tube, and a dropping funnel, Add 1 / 3 of the second solution Agent , 1 / 3 of the initiator solution, 2 / 3 of the reaction monomer mixture, introduce N2, control the stirring speed to 300-500rpm, gradually heat to 80℃ and react for 2h, mix 1 / 3 of the initiator solution and the remaining 1 / 3 of the reaction monomer mixture evenly and then add dropwise, continue to react for 2h after the addition is complete, finally continue to dropwise add the remaining 1 / 3 of the initiator solution, react for 3-4h after the addition is complete, cool to below 60℃ after the reaction is complete, add the second solvent to adjust the solid content to 40%, filter the material to obtain a cellulose derivative modified acrylate polymer;
[0029] S2: fully stirring the cellulose derivative modified acrylate polymer and the first solvent, and then sequentially adding an antistatic agent, a wetting agent and a curing agent, and mixing them evenly to obtain a pressure-sensitive adhesive.
[0030] In addition, to achieve the above-mentioned purpose, the present invention also provides an application of a pressure-sensitive adhesive in a high-temperature resistant "0" climb large-size polarizer protective film.
[0031] Preferably, the protective film comprises a PET substrate provided with an antistatic layer, a release film layer and a pressure-sensitive adhesive layer located therebetween.
[0032] Preferably, the preparation method of the protective film is as follows:
[0033] After defoaming, the pressure-sensitive adhesive is evenly coated on the side of the PET substrate away from the antistatic layer. After drying, a pressure-sensitive adhesive layer is formed on the surface of the PET substrate. Subsequently, a release film is covered on one side of the pressure-sensitive adhesive layer to obtain the high-temperature resistant "0 climb" large-size polarizer protective film.
[0034] Preferably, the pressure-sensitive adhesive layer has a thickness of 10-20 μm; more preferably, the thickness is 14 μm.
[0035] Preferably, the PET substrate is a PET optical film with a thickness of 25-75 μm and antistatic treatment on one side; more preferably, the thickness is 38 μm.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The present invention provides a pressure-sensitive adhesive for use in a high-temperature resistant "0" climb large-size polarizer protective film. Specifically, firstly, a polymerization reaction is carried out through an acrylate hard monomer, an acrylate soft monomer, an acrylate functional monomer and a cellulose derivative containing a double bond to obtain a cellulose derivative modified acrylic polymer, and an antistatic agent, a wetting agent, and an isocyanate curing agent are added and mixed evenly, and then coated on the side of the PET substrate away from the antistatic layer, and after drying, a release film is covered on one side of the pressure-sensitive adhesive layer to form the protective film. The acrylate polymer introduces cellulose molecules into the acrylate polymer through double bond polymerization. Cellulose is a polymer formed by connecting glucose molecules through β-1,4-glycosidic bonds, which has high stability and certain lubricating properties. The skeleton support of cellulose molecules improves the toughness of the pressure-sensitive adhesive and its ability to resist deformation by external forces, and reduces the creep of the pressure-sensitive adhesive. Under high temperature conditions, due to the supporting and protective effect of the spatial skeleton of the cellulose macromolecule, the creep of the molecules is greatly reduced. At the same time, the self-lubricating property of cellulose makes the peeling force of the protective film climb very little after cooling, and a low high-speed peeling force can still be obtained.
[0038] 2. The present invention provides a high-temperature resistant "0" climb protective film for large-size polarizers. The low-speed peeling force of the protective film can reach 5gf / 25mm, the high-speed peeling force is as low as 50gf / 25mm, the surface resistivity is less than 1.0*10^12Ω, and the film-tearing voltage is less than 400V. The protective film has good performance stability. The low-speed peeling force, high-speed peeling force, surface resistivity, and film-tearing voltage measured after long-term bonding are still at the above levels. After aging at 85℃*500h after bonding, the back sticker becomes free of residue and precipitation. After cooling, the low-speed peeling force and high-speed peeling force measured have a climbing amplitude of less than 30%, and the surface resistivity and film-tearing voltage are still comparable to the initial data. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Unless otherwise specified, the reagents or materials described in the following examples are common commercially available products.
[0041] Example 1
[0042] S1. First, mix the acrylic acid ester hard monomer, acrylic acid ester soft monomer, acrylic acid ester functional monomer, and cellulose derivative containing double bonds uniformly, and dissolve the initiator in Secondary solvent Prepare a 5% initiator solution in ethyl acetate;
[0043] Then in a four-necked flask equipped with an electric stirrer, condenser, N2 catheter, and dropping funnel, Add 1 / 3 of the second solution Agent , 1 / 3 of the initiator solution, 2 / 3 of the reaction monomer mixture, introduce N2, control the stirring speed to 300-500rpm, gradually heat to 80℃ and react for 2h, mix 1 / 3 of the initiator solution and the remaining 1 / 3 of the reaction monomer mixture evenly and then add dropwise, continue to react for 2h after the addition is complete, finally continue to dropwise add the remaining 1 / 3 of the initiator solution, react for 3-4h after the addition is complete, cool to below 60℃ after the reaction is complete, add Secondary solvent The solid content is adjusted to 40%, and filtered to obtain a cellulose derivative modified acrylate polymer;
[0044] S2: Add 100 parts by weight of the cellulose derivative modified acrylate polymer and 40 parts by weight of the first solvent (toluene) into a beaker, and stir them at a speed of 300-500 rpm for 5 minutes; then add 2 parts by weight of an antistatic agent (FC4400 of 3M), 1 part by weight of a wetting agent (polyether modified organosiloxane SY5066), and 2 parts by weight of a curing agent (toluene diisocyanate (TDI) trimer) in sequence, and mix at a speed of 300-500 rpm for 10-15 minutes to obtain a pressure-sensitive adhesive (a solution at this time);
[0045] S3 allows the pressure-sensitive adhesive to defoam for 5 minutes, then uses a coating machine to evenly apply the adhesive solution on the side of the PET substrate that has not been treated with antistatic agents, places it in a 100°C oven and bakes it for 2 minutes to form a dry adhesive layer (i.e., a pressure-sensitive adhesive layer), takes it out, covers it with a release film, and places it in a 35°C oven for 3 days to obtain the high-temperature resistant "0 climb" large-size polarizer protective film.
[0046] The types and weight fractions of the components in the cellulose derivative-modified acrylic ester polymer are as follows, and the weight fraction units in S1 and S2 are the same.
[0047] Acrylate hard monomer: 30 parts of methyl acrylate, 20 parts of vinyl acetate;
[0048] Acrylate soft monomer: 100 parts of isooctyl acrylate, 40 parts of octadecyl acrylate;
[0049] Acrylate functional monomer: 5 parts of polyethylene glycol diacrylate, 10 parts of hydroxyethyl acrylate;
[0050] Cellulose derivatives containing double bonds: 30 parts;
[0051] Second solvent: 350 parts;
[0052] Initiator: 2 parts.
[0053] Example 2
[0054] Compared with Example 1, the types and weight fractions of the components in the cellulose derivative-modified acrylate polymer were changed, and the other steps and parameters remained unchanged.
[0055] The types and mass fractions of the components in the cellulose derivative modified acrylic ester polymer are as follows:
[0056] Acrylate hard monomer: 30 parts of isobutyl methacrylate, 10 parts of acrylic acid;
[0057] Acrylate soft monomer: 60 parts of 2-ethylhexyl acrylate, 50 parts of nonyl acrylate;
[0058] Acrylate functional monomer: 15 parts of hydroxyethyl acrylate, 10 parts of 2-methoxyethyl acrylate;
[0059] Cellulose derivatives containing double bonds: 40 parts;
[0060] Second solvent: 320 parts;
[0061] Initiator: 1.5 parts.
[0062] Example 3
[0063] Compared with Example 1, the mass fractions of the cellulose derivative-modified acrylate polymer, the first solvent, the antistatic agent, the wetting agent, and the curing agent were changed, and the other steps and parameters remained unchanged.
[0064] The weight proportions of each component after the change are as follows:
[0065] Cellulose derivative modified acrylate polymer: 80 parts
[0066] Antistatic agent: 1.5 parts
[0067] Wetting agent: 0.7 parts
[0068] Curing agent: 1.5 parts
[0069] First solvent: 35 parts.
[0070] Example 4
[0071] Compared with Example 1, the mass fractions of the cellulose derivative-modified acrylate polymer, the first solvent, the antistatic agent, the wetting agent, and the curing agent were changed, and the other steps and parameters remained unchanged.
[0072] The weight proportions of each component after the change are as follows:
[0073] Cellulose derivative modified acrylate polymer: 90 parts
[0074] Antistatic agent: 2.5 parts
[0075] Wetting agent: 2 parts
[0076] Curing agent: 4 parts
[0077] First solvent: 35 parts;
[0078] Comparative Example 1
[0079] The only difference between this comparative example and Example 1 is that no cellulose derivative containing double bonds is added, and the remaining steps and parameters are the same.
[0080] Comparative Example 2
[0081] The only difference between this comparative example and Example 1 is that no cellulose derivative containing double bonds is added in this comparative example, but an equal amount of cellulose derivative is mixed into the protective film coating liquid made of the pressure-sensitive adhesive prepared in Comparative Example 2.
[0082] The performance tests were performed on the polarizer protective films prepared in Examples 1 to 4 and Comparative Examples 1 to 2, respectively, to obtain the test results shown in Table 1 below.
[0083] The performance test methods in the table are as follows:
[0084] (1) Peel force test: The test was conducted in accordance with the national standard GB / T 2792-2014. The prepared protective film (90×25 mm) was pasted on the surface of the back sticker (304 mirror steel plate or polarizer), and rolled back and forth 3 times with a 2 kg roller. After being placed in an environment of (22±2)℃*(50±5)%RH for 20 minutes, a 180° peel force test was performed using a peel force tester. The low speed peel force test speed was 300 mm / min, and the high speed peel force test speed was 30000 mm / min.
[0085] (2) High-temperature peel strength test: The prepared protective film (90×25 mm) was pasted on a 304 mirror steel plate and rolled back and forth three times with a 2 kg roller. The film was placed in an oven at 85°C for 500 h. After being taken out and placed in an environment of (22±2)°C*(50±5)%RH for 2 h, the film was tested by a peel strength tester. The low-speed peel strength test speed was 300 mm / min, and the high-speed peel strength test speed was 30000 mm / min.
[0086] (3) Surface resistivity test: Cut the protective film into A4 size, remove the release film, and test the surface resistivity on a high resistance meter with the pressure-sensitive adhesive layer facing upward.
[0087] (4) Aging test: Cut the protective film into A4 size, attach it to the surface of the polarizer, and put it in an aging oven. The aging conditions are 85℃*85%RH*500h. After taking it out and cooling it, observe whether there are any abnormal phenomena such as bubbling or floating on the surface. Then tear off the protective film and observe whether there is any residual glue or residue on the surface of the object.
[0088] Table 1
[0089]
[0090]
[0091] From the test results of Examples 1-4 and Comparative Examples 1-2 in Table 1, it can be seen that the high temperature resistant "0 climb" large-size polarizer surface protection film prepared by the present invention, after being treated at room temperature for 180d and 85°C*85%RH*500h, the climbing amplitudes of the low-speed (300mm / min) peeling force and the high-speed (30000mm / min) peeling force are both very small, and the surface resistivity, film tearing voltage and optical properties meet the requirements.
[0092] In Comparative Example 1, other conventional heat-resistant monomers are used, and the initial high-speed peeling force is relatively small. After long-term placement or high-temperature baking, the adhesive layer creeps, resulting in an increase in the bonding area, and the peeling force rises significantly higher than the present invention.
[0093] In Comparative Example 2, a cellulose derivative without double bonds is directly blended into the glue. Since the cellulose derivative is in a free state in the glue layer, the creep of the obtained protective film is very small after being placed at room temperature for a long time or baked. Therefore, the increase of the low-speed (300 mm / min) peeling force and the high-speed peeling force (30000 mm / min) is very small, but the optical properties of the film decrease after aging.
Claims
1. A pressure-sensitive adhesive, characterized in that: It includes the following components by weight: 80-100 parts of cellulose derivative modified acrylate polymer, 1-3 parts of curing agent, 1-5 parts of antistatic agent, 0.5-3 parts of wetting agent and 30-50 parts of first solvent; The cellulose derivative modified acrylate polymer is obtained by free radical polymerization of acrylate hard monomer, acrylate soft monomer, acrylate functional monomer, cellulose derivative containing double bonds, initiator and second solvent.
2. A pressure-sensitive adhesive according to claim 1, characterized in that: The acrylic acid ester hard monomer is one or more of acrylic acid, methacrylic acid, methyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, vinyl acetate, styrene and acrylonitrile.
3. A pressure-sensitive adhesive according to claim 1, characterized in that: The acrylic acid ester soft monomer is one or more of 2-ethylhexyl acrylate, isooctyl acrylate, n-butyl acrylate, isobutyl acrylate, nonyl acrylate, dodecyl acrylate, octadecyl acrylate and cyclohexyl methacrylate.
4. A pressure-sensitive adhesive according to claim 1, characterized in that: The acrylate functional monomer is one of hydroxyethyl acrylate, hydroxypropyl acrylate, 1,6-hexanediol diacrylate, 2-methoxyethyl acrylate, polyethylene glycol diacrylate, 3-ethoxyethyl acrylate, and 2-phenoxyethyl acrylate.
5. A pressure-sensitive adhesive according to claim 1, characterized in that: The double bond-containing cellulose derivative is obtained by reacting a double bond-containing acyl halide compound with a hydroxyl group in the cellulose derivative.
6. A method for preparing a pressure-sensitive adhesive according to any one of claims 1 to 5, characterized in that: The steps include: S1 prepares cellulose derivative modified acrylate polymer; S2: fully stirring the cellulose derivative modified acrylate polymer and the first solvent, and then sequentially adding an antistatic agent, a wetting agent and a curing agent, and mixing them evenly to obtain a pressure-sensitive adhesive.
7. Application of a pressure-sensitive adhesive according to any one of claims 1 to 5 in a high temperature resistant "0" climb large-size polarizer protective film.
8. The use of a pressure-sensitive adhesive according to claim 7 in a high temperature resistant "0" climb large-size polarizer protective film, characterized in that: The protective film comprises a PET substrate provided with an antistatic layer, a release film layer and a pressure-sensitive adhesive layer located therebetween.
9. The use of a pressure-sensitive adhesive according to claim 8 in a high temperature resistant "0" climb large-size polarizer protective film, characterized in that: The preparation method of the protective film is as follows: After defoaming, the pressure-sensitive adhesive is evenly coated on the side of the PET substrate away from the antistatic layer. After drying, a pressure-sensitive adhesive layer is formed on the surface of the PET substrate. Subsequently, a release film is covered on one side of the pressure-sensitive adhesive layer to obtain the high-temperature resistant "0 climb" large-size polarizer protective film.
10. The use of a pressure-sensitive adhesive according to claim 7 in a high temperature resistant "0" climb large-size polarizer protective film, characterized in that: The thickness of the pressure-sensitive adhesive layer is 10-20 um.
Citation Information
Patent Citations
Adhesive combination and surface protective film
CN102746810A
Cited By
High-performance release film for polaroid
CN121500466A